2000
DOI: 10.1046/j.1524-475x.2000.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell, matrix changes and alpha‐smooth muscle actin expression in repair of the canine meniscus

Abstract: Processes in the repair of a crevice in the knee joint meniscus were investigated in 10 dogs. Two 2-mm cylindrical plugs from each medial meniscus were removed, rendered acellular by freezing and thawing, and then reinserted into the meniscus. Dogs were euthanized at intervals of 3-52 weeks after surgery. The crevice between the plug and meniscus at 3 weeks after surgery was filled with a tissue containing alpha-smooth muscle actin-positive cells. One year after surgery, the plug had remodeled and was populate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 35 publications
4
47
2
1
Order By: Relevance
“…Cell accumulation, presumably due to a combination of migration and proliferation, appears to be an important component of meniscal repair in vivo, and previous studies have shown complete repopulation of meniscal allografts (45) or a devitalized meniscal plug that was reinserted into the meniscus in an animal model (46). In the present study, cell accumulation at the interface was associated with increased tissue formation and interfacial shear strength of repair.…”
Section: Discussionsupporting
confidence: 65%
“…Cell accumulation, presumably due to a combination of migration and proliferation, appears to be an important component of meniscal repair in vivo, and previous studies have shown complete repopulation of meniscal allografts (45) or a devitalized meniscal plug that was reinserted into the meniscus in an animal model (46). In the present study, cell accumulation at the interface was associated with increased tissue formation and interfacial shear strength of repair.…”
Section: Discussionsupporting
confidence: 65%
“…Early studies investigating the use of xenogeneic meniscal tissue aimed only to kill the xenogeneic cells using freeze-thaw techniques and made no attempts to remove residual xenoantigens. 37,38 However, the presence of foreign antigens may result in antibody-dependant inflammation that has the potential to result in tissue damage and calcification. The challenge was to decellularize the dense fibrous matrix of the porcine medial meniscus whilst also removing major xenoantigens, leaving an acellular, biocompatible scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…A number of histological studies have also attempted to define the fine structure of the meniscus (Cheung 1987;Bland and Ashhurst 1996;Wildey and McDevitt 1998;Kambic et al 2000;Wildey et al 2001;Ahluwalia et al 2001;Hellio Le Graverand et al 2001a, b, c, d;Naumann et al 2002;Rijk et al 2004;Meister et al 2004;Kobayashi et al 2004;Kambic and McDevitt 2005). The material properties of the meniscus, however, make it a technically demanding tissue to be examined histologically and particular care must be taken to ensure that artefacts are not introduced into specimens during histological processing.…”
Section: Introductionmentioning
confidence: 99%
“…Kambic et al (2000) and Ahluwalia et al (2001) demonstrated that a proportion of meniscal cells expressed a-smooth muscle cell actin and a similar contractile phenotype to myofibroblasts with possibly a role to play in wound retraction. Four classes of cells have been identified in the rabbit meniscus by visualisation of cytoskeletal proteins, cytoplasmic extensions and gap junctions between the various cell types (Hellio Le Graverand et al 2001a, d).…”
Section: Introductionmentioning
confidence: 99%